2014
DOI: 10.1093/humupd/dmu056
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear progesterone receptor isoforms in uterine pathophysiology

Abstract: PRs are key mediators of progesterone action in uterine tissues and are essential for normal uterine function. Aberrant PR function (due to abnormal expression and/or function) is a major cause of uterine pathophysiology. Further investigation of the underlying mechanisms of PR isoform action in the uterus is required, as this knowledge will afford the opportunity to create progestin/PR-based therapeutics to treat various uterine pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
239
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(265 citation statements)
references
References 295 publications
(284 reference statements)
4
239
1
11
Order By: Relevance
“…Progesterone affects the vaginal epithelium and cervical mucus, making it thick and impenetrable to sperm. Progesterone is anti-mitogenic in endometrial epithelial cells, and as such, mitigates the tropic effects of estrogen 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone affects the vaginal epithelium and cervical mucus, making it thick and impenetrable to sperm. Progesterone is anti-mitogenic in endometrial epithelial cells, and as such, mitigates the tropic effects of estrogen 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Its presence is only observed in appreciable amounts during the luteal phase as its source is the corpus luteum, and its primary role during this time period is in endometrial remodeling as well as endometrial angiogenesis in preparation for the arrival of an early embryo (Patel B, 2014). While this effect is critical for the maintenance of pregnancy, just as important is the inhibitory role that P4 has -along with estrogen and inhibin -on the pituitary gonadotropins follicle stimulating hormone (FSH) and luteinizing hormone (LH), respectively (Lesoon LA, 1992).…”
Section: The Progesterone Receptor -To Be or Not To Be: The Anti-inflmentioning
confidence: 99%
“…PR exists in two isoforms PRA and PRB, which are transcribed from two promoters on a single gene [15,16] . Although PRB functions as a transcriptional activator of Pg responsive genes, PRA may function as a transcriptional inhibitor [17,18] . Several studies have demonstrated that PR is upregulated in uterine leiomyomata, as compared with adjacent normal myometrium [19] at mRNA and protein levels.…”
Section: Mechanism Of Actionmentioning
confidence: 99%